2007
DOI: 10.1037/1076-898x.13.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Consumer credit card use: The roles of creditor disclosure and anticipated emotion.

Abstract: In response to federal legislative reform aimed, in part, at reducing consumer bankruptcy filings, the authors conducted 2 experiments examining the role of affect in purchasing behavior. In Experiment 1, they examined consumer debtors, and in Experiment 2, they examined nondebtors. In both experiments, they investigated purchasing decisions made during a simulated online shopping trip, with some participants receiving standard disclosures of interest rates and money owed and with other participants receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Likewise, future research should also consider how consumer emotion might also moderate the effect of CTA readership on CTA comprehension and CTA shopping. In the context of federally mandated consumer credit disclosures, Wiener, et al (2007) found that for some consumers, the enhanced disclosures resulted in negative affect and corresponding mood repair leading consumers to engage in more (rather than less) shopping to alleviate the negative emotional response precipitated by the disclosures. To the extent CTA readership results in similar awareness of contract risks, emotion may play a comparable role in shaping consumer behavior.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, future research should also consider how consumer emotion might also moderate the effect of CTA readership on CTA comprehension and CTA shopping. In the context of federally mandated consumer credit disclosures, Wiener, et al (2007) found that for some consumers, the enhanced disclosures resulted in negative affect and corresponding mood repair leading consumers to engage in more (rather than less) shopping to alleviate the negative emotional response precipitated by the disclosures. To the extent CTA readership results in similar awareness of contract risks, emotion may play a comparable role in shaping consumer behavior.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Understanding why consumers read or don't read CTAs is fundamentally a question about psychological processes, making examination of these processes a natural starting point for reform proposals aimed at correcting the problems associated with non-readership. Yet while psychologists have begun to study consumer reading behavior in some domains such as credit card disclosures (Wiener, Winter, Cantone, Gross & Block-Lieb, 2007), psychologists have yet to focus on consumer behavior when presented with CTAs. Accordingly, reform proposals aimed at CTA nonreadership have therefore had to rely on general models of human behavior that may fail to reflect actual psychological functioning in the CTA context.…”
Section: A Social Psychological Investigation Of Non-readership Of CLmentioning
confidence: 99%
“…The use of these 16 clips to induce emotions was further supported by Rottenberg, Ray, and Gross (2007), which provides a primer on the use of film clips to elicit emotions in experimental settings. Despite being a relatively new research paradigm, emotion has been successfully induced in online experimental designs in a variety of ways, including the Velten procedure, autobiographical recall, moodsuggestive photographs, picture-illustrated emotive texts, and video clips (Göritz, 2007;Göritz & Moser, 2006;Verheyen & Göritz, 2009;Verleuer, Verhagen, & Heuvelman, 2007;Wiener et al, 2007), so I expected that video clips shown online would be a successful means of emotion induction (such clips are agreed to be among the most robust means of emotion induction; see Gross & Levenson, 1995;Lench, et al, 2011;Martin, 1990;Philippot, 1993;Rottenberg, Ray, & Gross, 2007;Schaefer, et al, 2010;Westermann et al, 1996 …”
Section: Discussionmentioning
confidence: 99%
“…Objections having to do with research settings can be assuaged (though certainly not dismissed outright) as online research paradigms have been found to be largely comparable to traditional "in person" methods (Gosling, Vazire, Srivastava, & John, 2004) and more specific to the current study, emotion has been successfully induced in past online research (Wiener et al, 2007).…”
Section: Study Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation